Does experience sharing affect farmers' pro-environmental behavior? A randomized controlled trial in Vietnam. (December 2020) - Vu, Ha Thu; Tran, Duc; Goto, Daisaku; Kawata, Keisuke
Highlights: We examine the effect of an information treatment via "peer farmers" and a 50% price subsidy treatment on organic fertilizer adoption. We conduct a randomized controlled trial with 1287 tea-cultivating farmers in Vietnam. Both treatments have significant impacts on farmers' adoption of organic fertilizer. The information treatment is approximately one-third as effective as the subsidy treatment. The information treatment performs well for members of certification groups. Abstract: Encouraging farmers to adopt pro-environmental production is vital to the promotion of sustainable agriculture. Previous observational studies emphasize the importance of economic incentives and information access to farmers' decision-making processes; however, due to endogeneity issues, little strong causal evidence is available. This study makes an original contribution by experimentally examining the impacts of the 50% price subsidy and information treatments on farmers' adoption of organic fertilizer. A short video sharing the experience of farmers who have applied organic fertilizer is selected as our information treatment. We analyze data from a randomized controlled trial (RCT) conducted with 1287 small-scale tea farmers in Vietnam. We find significant impacts of both the information and 50% price subsidy treatments. Moreover, the effect of the former is approximately one-third that of the latter. Subgroup treatment analysis also reveals that the information treatment performs well for members of certification groups. Thus, to induce farmers to adopt pro-environmental production behaviors, information treatment can partially substitute for subsidies to reduce the burden on the public budget.